(untitled) (Biological Sciences - PJSIR, 2005)
Six different alkyds were formulated with crude rubber seed oil 45% (1), 50% (II) and 55% (III); refined rubber seed oil 45% (IV), 50% (V) and 55% (VI); phthalic anhydride and glycerol. All the alkyds were formulated to alkyd constant of about 1.0. The alcoholysis method was used. Refining enhanced the quality of rubber seed oil in alkyd resin manufacture. The properties of the finished alkyd resins such as viscosity, number average molecular weights, drying schedule, chemical resistance and film hardness were determined. The intrinsic viscosity (h) was observed to be proportional to the number average molecular weight of the two sets of alkyd resins. However, samples I-III exhibited higher intrinsic viscosity in toluene than samples IV-VI. On the contrary, the films of samples IV-VI were harder, dried faster, and were more chemically resistant than those of samples I-III. The practical implications of these results are discussed.